Adam Ledger

Mr. Adam Ledger

335 Reputation

11 Badges

4 years, 276 days
unemployed
hobo
Perth, Australia

Social Networks and Content at Maplesoft.com

MaplePrimes Activity


These are questions asked by Adam Ledger

Series 2:Hi i was wondering if someone could explain how i can get series like this to evaluate to infinity, or a float placeholder for i mean.

Series 1:Any then also explain the mathematics as to how the this series converges to a negative limit please.

seq(evalf[10](eval(sum(2^n*floor(2^n), n = 1 .. N), [N = 10^k])), k = 1 .. 3)

1398100., 0.2142584059e61, 0.1530840927e603

(1)

evalf[10](sum(2^n*floor(2^n), n = 1 .. infinity))

-1.333333333

(2)

``


 

Download WHY_NO_EVAL.mw


 

seq(evalf[10](eval(sum(5^(n-1)*floor((1/4)*5^n), n = 1 .. N), [N = 10^k])), k = 1 .. 3)

0.4967053121e13, 0.3241153791e139, 0.4536359279e1397

(1)

evalf[10](sum(5^(n-1)*floor((1/4)*5^n), n = 1 .. infinity))

sum(5^(n-1)*floor((1/4)*5^n), n = 1 .. infinity)

(2)

``


 

Download WHY_NO_EVAL.mw

In the original worksheet that these were produced, upon closing the within set brackets they do not reduce to the unique elements. But in copying the output to a new worksheet as shown, they do reduce.


 

{Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = -2}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 0}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 1, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = -1, (2, 2) = 1, (2, 3) = 0, (3, 1) = 1, (3, 2) = 2, (3, 3) = 1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = -1, (3, 2) = 0, (3, 3) = -2}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = -1, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 1, (3, 1) = 0, (3, 2) = 0, (3, 3) = 2})}

{Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = -2}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 0}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 1, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = -1, (2, 2) = 1, (2, 3) = 0, (3, 1) = 1, (3, 2) = 2, (3, 3) = 1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = -1, (3, 2) = 0, (3, 3) = -2}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = -1, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 1, (3, 1) = 0, (3, 2) = 0, (3, 3) = 2})}

(1)

restart; with(LinearAlgebra)

{Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = -2}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 0}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 1, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = -1, (2, 2) = 1, (2, 3) = 0, (3, 1) = 1, (3, 2) = 2, (3, 3) = 1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = -1, (3, 2) = 0, (3, 3) = -2}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = -1, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 1, (3, 1) = 0, (3, 2) = 0, (3, 3) = 2})}

{Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = -2}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 0}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = 1, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = -1, (2, 2) = 1, (2, 3) = 0, (3, 1) = 1, (3, 2) = 2, (3, 3) = 1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = -1, (3, 2) = 0, (3, 3) = -2}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 0, (3, 1) = 0, (3, 2) = -1, (3, 3) = -1}), Matrix(3, 3, {(1, 1) = 0, (1, 2) = 0, (1, 3) = 0, (2, 1) = 0, (2, 2) = 0, (2, 3) = 1, (3, 1) = 0, (3, 2) = 0, (3, 3) = 2})}

(2)

``


 

Download JESUS_MATRIX.mw

I think that maple is actually evaluating this series into what ever ridiculously long closed form expression the expansion of the series has, but i just want the latex for what i have entered.

How do i tell maple to not evaluate something?
 

latex(a[p, q] = sum(cos(2*Pi*(p+1)*(n-1)/q), n = 1 .. q))

a_{{p,q}}= \left( -4\, \left( \cos \left( {\frac {\pi }{q}} \right)
 \right) ^{2}+8\, \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{2} \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{
2}-8\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {

\pi \,p}{q}} \right) \sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right) +3-4\, \left( \cos \left( {\frac {
\pi \,p}{q}} \right)  \right) ^{2} \right)  \left( \cos \left( {\frac
{\pi \, \left( q+1 \right) }{q}} \right)  \right) ^{2}+ \left( -4\,
 \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}+8\,
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \left(
\cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8\,\sin \left( {
\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}} \right)
\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}}
 \right) +3-4\, \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{2} \right)  \left( \cos \left( {\frac {\pi \, \left( q+1
 \right) p}{q}} \right)  \right) ^{2}+ \left( 8\, \left( \cos \left( {
\frac {\pi }{q}} \right)  \right) ^{2}-16\, \left( \cos \left( {\frac
{\pi \,p}{q}} \right)  \right) ^{2} \left( \cos \left( {\frac {\pi }{q
}} \right)  \right) ^{2}+16\,\sin \left( {\frac {\pi \,p}{q}} \right)
\cos \left( {\frac {\pi \,p}{q}} \right) \sin \left( {\frac {\pi }{q}}
 \right) \cos \left( {\frac {\pi }{q}} \right) -6+8\, \left( \cos
 \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \right)  \left(
\cos \left( {\frac {\pi \, \left( q+1 \right) p}{q}} \right)  \right)
^{2} \left( \cos \left( {\frac {\pi \, \left( q+1 \right) }{q}}
 \right)  \right) ^{2}+ \left( 8\,\sin \left( {\frac {\pi \,p}{q}}
 \right) \cos \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left(
{\frac {\pi }{q}} \right)  \right) ^{4}-4\, \left( \cos \left( {\frac
{\pi }{q}} \right)  \right) ^{3}\sin \left( {\frac {\pi }{q}} \right)
+8\, \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2}
 \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{3}\sin
 \left( {\frac {\pi }{q}} \right) -4\,\sin \left( {\frac {\pi \,p}{q}}
 \right) \cos \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left(
{\frac {\pi }{q}} \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi \,p
}{q}} \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{3} \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{
2}-8\,\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{
q}} \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right)
^{4}+\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q
}} \right) +4\, \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{2}\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac
{\pi }{q}} \right) +4\,\sin \left( {\frac {\pi \,p}{q}} \right)
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{3}-\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right)  \right) \sin \left( {\frac {\pi \, \left( q+1 \right) }{q}}
 \right) \cos \left( {\frac {\pi \, \left( q+1 \right) }{q}} \right)
 \left( - \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2
}+ \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2} \right)
^{-1}+ \left( 8\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos \left(
{\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{4}-4\, \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{3}\sin \left( {\frac {\pi }{q}} \right) +8\,
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \left(
\cos \left( {\frac {\pi }{q}} \right)  \right) ^{3}\sin \left( {\frac
{\pi }{q}} \right) -4\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos
 \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac {\pi }
{q}} \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi \,p}{q}}
 \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{3
} \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8\,\sin
 \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}}
 \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{4
}+\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}}
 \right) +4\, \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{2}\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac
{\pi }{q}} \right) +4\,\sin \left( {\frac {\pi \,p}{q}} \right)
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{3}-\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right)  \right) \sin \left( {\frac {\pi \, \left( q+1 \right) p}{q}}
 \right) \cos \left( {\frac {\pi \, \left( q+1 \right) p}{q}} \right)
 \left( - \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2
}+ \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2} \right)
^{-1}-2\, \left( 8\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos
 \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac {\pi }
{q}} \right)  \right) ^{4}-4\, \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{3}\sin \left( {\frac {\pi }{q}} \right) +8\,
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \left(
\cos \left( {\frac {\pi }{q}} \right)  \right) ^{3}\sin \left( {\frac
{\pi }{q}} \right) -4\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos
 \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac {\pi }
{q}} \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi \,p}{q}}
 \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{3
} \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8\,\sin
 \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}}
 \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{4
}+\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}}
 \right) +4\, \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{2}\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac
{\pi }{q}} \right) +4\,\sin \left( {\frac {\pi \,p}{q}} \right)
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{3}-\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right)  \right)  \left( \cos \left( {\frac {\pi \, \left( q+1
 \right) p}{q}} \right)  \right) ^{2}\sin \left( {\frac {\pi \,
 \left( q+1 \right) }{q}} \right) \cos \left( {\frac {\pi \, \left( q+
1 \right) }{q}} \right)  \left( - \left( \cos \left( {\frac {\pi \,p}{
q}} \right)  \right) ^{2}+ \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{2} \right) ^{-1}-2\, \left( 8\,\sin \left( {\frac
{\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}} \right)
 \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{4}-4\,
 \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{3}\sin
 \left( {\frac {\pi }{q}} \right) +8\, \left( \cos \left( {\frac {\pi
\,p}{q}} \right)  \right) ^{2} \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{3}\sin \left( {\frac {\pi }{q}} \right) -4\,\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right)  \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8
\,\sin \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac
{\pi \,p}{q}} \right)  \right) ^{3} \left( \cos \left( {\frac {\pi }{q
}} \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right)  \left( \cos \left( {\frac {\pi \,p}
{q}} \right)  \right) ^{4}+\sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right) +4\, \left( \cos \left( {\frac {\pi
\,p}{q}} \right)  \right) ^{2}\sin \left( {\frac {\pi }{q}} \right)
\cos \left( {\frac {\pi }{q}} \right) +4\,\sin \left( {\frac {\pi \,p}
{q}} \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{3}-\sin \left( {\frac {\pi \,p}{q}} \right) \cos \left( {
\frac {\pi \,p}{q}} \right)  \right) \sin \left( {\frac {\pi \,
 \left( q+1 \right) p}{q}} \right) \cos \left( {\frac {\pi \, \left( q
+1 \right) p}{q}} \right)  \left( \cos \left( {\frac {\pi \, \left( q+
1 \right) }{q}} \right)  \right) ^{2} \left( - \left( \cos \left( {
\frac {\pi \,p}{q}} \right)  \right) ^{2}+ \left( \cos \left( {\frac {
\pi }{q}} \right)  \right) ^{2} \right) ^{-1}+ \left( -8\, \left( \cos
 \left( {\frac {\pi }{q}} \right)  \right) ^{2}+16\, \left( \cos
 \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \left( \cos \left(
{\frac {\pi }{q}} \right)  \right) ^{2}-16\,\sin \left( {\frac {\pi \,
p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}} \right) \sin \left( {
\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}} \right) +6-8\,
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2}
 \right) \sin \left( {\frac {\pi \, \left( q+1 \right) p}{q}} \right)
\cos \left( {\frac {\pi \, \left( q+1 \right) p}{q}} \right) \sin
 \left( {\frac {\pi \, \left( q+1 \right) }{q}} \right) \cos \left( {
\frac {\pi \, \left( q+1 \right) }{q}} \right) - \left( -4\, \left(
\cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}+8\, \left( \cos
 \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \left( \cos \left(
{\frac {\pi }{q}} \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi \,p
}{q}} \right) \cos \left( {\frac {\pi \,p}{q}} \right) \sin \left( {
\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}} \right) +3-4\,
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2}
 \right)  \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-
 \left( -4\, \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2
}+8\, \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2}
 \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8\,\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right) \sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {
\pi }{q}} \right) +3-4\, \left( \cos \left( {\frac {\pi \,p}{q}}
 \right)  \right) ^{2} \right)  \left( \cos \left( {\frac {\pi \,p}{q}
} \right)  \right) ^{2}- \left( 8\, \left( \cos \left( {\frac {\pi }{q
}} \right)  \right) ^{2}-16\, \left( \cos \left( {\frac {\pi \,p}{q}}
 \right)  \right) ^{2} \left( \cos \left( {\frac {\pi }{q}} \right)
 \right) ^{2}+16\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos
 \left( {\frac {\pi \,p}{q}} \right) \sin \left( {\frac {\pi }{q}}
 \right) \cos \left( {\frac {\pi }{q}} \right) -6+8\, \left( \cos
 \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \right)  \left(
\cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \left( \cos
 \left( {\frac {\pi }{q}} \right)  \right) ^{2}- \left( 8\,\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right)  \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{4}-4
\, \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{3}\sin
 \left( {\frac {\pi }{q}} \right) +8\, \left( \cos \left( {\frac {\pi
\,p}{q}} \right)  \right) ^{2} \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{3}\sin \left( {\frac {\pi }{q}} \right) -4\,\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right)  \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8
\,\sin \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac
{\pi \,p}{q}} \right)  \right) ^{3} \left( \cos \left( {\frac {\pi }{q
}} \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right)  \left( \cos \left( {\frac {\pi \,p}
{q}} \right)  \right) ^{4}+\sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right) +4\, \left( \cos \left( {\frac {\pi
\,p}{q}} \right)  \right) ^{2}\sin \left( {\frac {\pi }{q}} \right)
\cos \left( {\frac {\pi }{q}} \right) +4\,\sin \left( {\frac {\pi \,p}
{q}} \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{3}-\sin \left( {\frac {\pi \,p}{q}} \right) \cos \left( {
\frac {\pi \,p}{q}} \right)  \right) \sin \left( {\frac {\pi }{q}}
 \right) \cos \left( {\frac {\pi }{q}} \right)  \left( - \left( \cos
 \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2}+ \left( \cos
 \left( {\frac {\pi }{q}} \right)  \right) ^{2} \right) ^{-1}- \left(
8\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,
p}{q}} \right)  \left( \cos \left( {\frac {\pi }{q}} \right)  \right)
^{4}-4\, \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{3}
\sin \left( {\frac {\pi }{q}} \right) +8\, \left( \cos \left( {\frac {
\pi \,p}{q}} \right)  \right) ^{2} \left( \cos \left( {\frac {\pi }{q}
} \right)  \right) ^{3}\sin \left( {\frac {\pi }{q}} \right) -4\,\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right)  \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8
\,\sin \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac
{\pi \,p}{q}} \right)  \right) ^{3} \left( \cos \left( {\frac {\pi }{q
}} \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right)  \left( \cos \left( {\frac {\pi \,p}
{q}} \right)  \right) ^{4}+\sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right) +4\, \left( \cos \left( {\frac {\pi
\,p}{q}} \right)  \right) ^{2}\sin \left( {\frac {\pi }{q}} \right)
\cos \left( {\frac {\pi }{q}} \right) +4\,\sin \left( {\frac {\pi \,p}
{q}} \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{3}-\sin \left( {\frac {\pi \,p}{q}} \right) \cos \left( {
\frac {\pi \,p}{q}} \right)  \right) \sin \left( {\frac {\pi \,p}{q}}
 \right) \cos \left( {\frac {\pi \,p}{q}} \right)  \left( - \left(
\cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2}+ \left( \cos
 \left( {\frac {\pi }{q}} \right)  \right) ^{2} \right) ^{-1}+2\,
 \left( 8\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos \left( {
\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{4}-4\, \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{3}\sin \left( {\frac {\pi }{q}} \right) +8\,
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \left(
\cos \left( {\frac {\pi }{q}} \right)  \right) ^{3}\sin \left( {\frac
{\pi }{q}} \right) -4\,\sin \left( {\frac {\pi \,p}{q}} \right) \cos
 \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac {\pi }
{q}} \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi \,p}{q}}
 \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{3
} \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8\,\sin
 \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}}
 \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{4
}+\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}}
 \right) +4\, \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{2}\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac
{\pi }{q}} \right) +4\,\sin \left( {\frac {\pi \,p}{q}} \right)
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{3}-\sin
 \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}}
 \right)  \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{2}\sin \left( {\frac {\pi }{q}} \right) \cos \left( {\frac
{\pi }{q}} \right)  \left( - \left( \cos \left( {\frac {\pi \,p}{q}}
 \right)  \right) ^{2}+ \left( \cos \left( {\frac {\pi }{q}} \right)
 \right) ^{2} \right) ^{-1}+2\, \left( 8\,\sin \left( {\frac {\pi \,p}
{q}} \right) \cos \left( {\frac {\pi \,p}{q}} \right)  \left( \cos
 \left( {\frac {\pi }{q}} \right)  \right) ^{4}-4\, \left( \cos
 \left( {\frac {\pi }{q}} \right)  \right) ^{3}\sin \left( {\frac {
\pi }{q}} \right) +8\, \left( \cos \left( {\frac {\pi \,p}{q}}
 \right)  \right) ^{2} \left( \cos \left( {\frac {\pi }{q}} \right)
 \right) ^{3}\sin \left( {\frac {\pi }{q}} \right) -4\,\sin \left( {
\frac {\pi \,p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}} \right)
 \left( \cos \left( {\frac {\pi }{q}} \right)  \right) ^{2}-8\,\sin
 \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left( {\frac {\pi
\,p}{q}} \right)  \right) ^{3} \left( \cos \left( {\frac {\pi }{q}}
 \right)  \right) ^{2}-8\,\sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right)  \left( \cos \left( {\frac {\pi \,p}
{q}} \right)  \right) ^{4}+\sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right) +4\, \left( \cos \left( {\frac {\pi
\,p}{q}} \right)  \right) ^{2}\sin \left( {\frac {\pi }{q}} \right)
\cos \left( {\frac {\pi }{q}} \right) +4\,\sin \left( {\frac {\pi \,p}
{q}} \right)  \left( \cos \left( {\frac {\pi \,p}{q}} \right)
 \right) ^{3}-\sin \left( {\frac {\pi \,p}{q}} \right) \cos \left( {
\frac {\pi \,p}{q}} \right)  \right) \sin \left( {\frac {\pi \,p}{q}}
 \right) \cos \left( {\frac {\pi \,p}{q}} \right)  \left( \cos \left(
{\frac {\pi }{q}} \right)  \right) ^{2} \left( - \left( \cos \left( {
\frac {\pi \,p}{q}} \right)  \right) ^{2}+ \left( \cos \left( {\frac {
\pi }{q}} \right)  \right) ^{2} \right) ^{-1}- \left( -8\, \left( \cos
 \left( {\frac {\pi }{q}} \right)  \right) ^{2}+16\, \left( \cos
 \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2} \left( \cos \left(
{\frac {\pi }{q}} \right)  \right) ^{2}-16\,\sin \left( {\frac {\pi \,
p}{q}} \right) \cos \left( {\frac {\pi \,p}{q}} \right) \sin \left( {
\frac {\pi }{q}} \right) \cos \left( {\frac {\pi }{q}} \right) +6-8\,
 \left( \cos \left( {\frac {\pi \,p}{q}} \right)  \right) ^{2}
 \right) \sin \left( {\frac {\pi \,p}{q}} \right) \cos \left( {\frac {
\pi \,p}{q}} \right) \sin \left( {\frac {\pi }{q}} \right) \cos
 \left( {\frac {\pi }{q}} \right)

 

``


 

Download MAPLE_PLEASE_HELPS_BECOZ_MAPLE_IS_FRENS.mw

Are we allowed to ask questions about only math or does it have to only be a problem with maple code?

I am getting this error for almost everything that i write in maple today, and i simply have no idea what causes it or what it means

 


 

"?SetOfCommonDivisors:=(X,Y)->{[[1,X intersect (map(numtheory:-divisors, Y))<>{???}],[0,otherwise]]??"

Error, unable to parse 'mverbatim'

"?SetOfCommonDivisors:=(X,Y)->{[[1,X intersect (map(numtheory:-divisors, Y))<>{???}],[0,otherwise]]??"

 

``


 

Download WTF_ERROR.mw

First 16 17 18 19 20 21 22 Last Page 18 of 34